Penampilan Fenotipik Buah Durian (Durio zibethinus Murr.) Di Kabupaten Dairi, Sumatera Utara - Andre Leo Horathius Saragih; Diana Sofia Hanafiah; Luthfi A.M. Siregar (Talenta Publisher, 2018)
Durian fruit is an exotic tropical fruit that has a unique flavor and aroma. Durian fruit is also called the king of fruits are very popular among various societies because of its peculiar taste. This research aimed to identify the morphological characteristic and phylogenetic relationship of durian in Sidikalang and Tanah Pinem district. The research was done at Sidikalang and Tanah Pinem district in November 2016 to February 2017 with survey method using durian descriptor of IPGRI. Sampling technique using purposive sampling with location judgement . The result of research showed that in Sidikalang and Tanah Pinem district there were 25genotipe of durian been identified. The closest relationship is obtained on G14 and G15 originating from Tanah Pinem District with a similarity value of 0,985. The furthest relationship was obtained from G13 and G15 from Tanah Pinem District with the similarity value of 6,115.